Public oblivion: Greek monuments of division and their impact on everyday culture wars (CAS Sofia Working Paper Series, 2024)
This paper discusses certain aspects of the dominant cultural heritage discourse in Greece, and their effects on the construction, preservation, and diffusion of public memory; although my case studies will not be archaeological as such, I will be discussing the materialities political power is imbued with, and the ways in which it regenerates itself at their expense (a process in which Greek archaeology often interferes). Focusing on what we generally call “alien monuments,” that is, monuments that do not form part of the hegemonic culture, the paper discusses minority legacies, as they strive to rescue themselves from centrally waged wars on memory, and oblivion.